2021
DOI: 10.1002/ptr.7200
|View full text |Cite
|
Sign up to set email alerts
|

What is the influence of cinnamon supplementation on liver enzymes? A systematic review and meta‐analysis of randomized controlled trials

Abstract: Existing evidence has uncovered the potential health benefits of cinnamon intake; however, its effect on liver function is unclear. Thus, the aim of this systematic review and meta-analysis was to examine the effect of cinnamon supplementation on liver enzymes. Relevant articles were identified through a systematic search in PubMed/Medline, Scopus, Web of Science, Cochrane Library, and Embase up to September 2020. All trials assessing the effect of oral cinnamon supplementation on serum levels of alanine amino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 65 publications
1
9
0
Order By: Relevance
“…We finally included four studies that fulfilled the eligibility criteria. Of these four studies, the study by Mousavi et al (2021 ) included alanine aminotransferase, aspartate aminotransferase, and alkaline phosphatase levels as outcomes that would indicate the safety of cinnamon supplementation with respect to liver enzymes. The authors found that cinnamon improved serum levels of hepatic enzymes in patients with type 2 diabetes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We finally included four studies that fulfilled the eligibility criteria. Of these four studies, the study by Mousavi et al (2021 ) included alanine aminotransferase, aspartate aminotransferase, and alkaline phosphatase levels as outcomes that would indicate the safety of cinnamon supplementation with respect to liver enzymes. The authors found that cinnamon improved serum levels of hepatic enzymes in patients with type 2 diabetes.…”
Section: Resultsmentioning
confidence: 99%
“…In terms of publication bias, Mousavi et al ( Mousavi et al, 2021 ) evaluated this bias using a funnel plot analysis and conducted Egger’s test. They found no small-study effects and no excessive significance bias.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The I ‐squared ( I 2 ) index was used to assess study heterogeneity. If the I 2 was greater than 50%, there was heterogeneity between the included trials (Mousavi et al, 2021). A sensitivity analysis was carried out to assess the potential bias and robustness of the overall effect estimate (Mousavi et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…If the I 2 was greater than 50%, there was heterogeneity between the included trials ( Mousavi et al, 2022 ). A sensitivity analysis was used to evaluate the potential bias and robustness of the overall effect estimate ( Mousavi et al, 2021 ). To determine the presence of publication bias, Egger’s regression test as well as funnel plot were used.…”
Section: Methodsmentioning
confidence: 99%